RESPONSE OF LOCAL CANDLENUT GRAIN WITH DIFFERENT DRYING DURATION TO GRAIN YIELD: RESPONS GABAH KEMIRI LOKAL DENGAN DURASI PENJEMURAN YANG BERBEDA TERHADAP HASIL GABAH - Maghfirah; Mulyanti; Lukman Martunis; Imelda (ROCE : Jurnal Pertanian Terapan, 2025)
Candlenut is a plant that has many uses and can be utilized as a basic ingredient for kitchen spices and pharmaceutical ingredients. The increasing demand for candlenuts from other countries makes farmers in Indonesia increasingly active in making candlenuts as the main crop Candlenut seeds have very high benefits and selling value if they have gone through a good and correct peeling process. This study aims to determine the effect of the length of time drying candlenut seeds processed with a peeling machine on the yield of candlenut grain. This research was conducted in Seulimum Village, Seulimum District, Aceh Besar in April 2024. This study used a non-factorial Randomized Block Design (RBD) of 4 treatments and 6 replications resulting in 24 experimental units. The parameters observed were the percentage of intact nuclei (%) and the percentage of broken nuclei (%). The results showed that the test treatment of the length of time drying candlenut seeds with sunlight with different intervals of the number of days did not give a significant effect on the percentage of intact candlenuts, and the percentage of broken nuclei.